Hubungan knowledge sharing dengan inovasi pengelola taman baca masyarakat di Jawa Barat - Yoshua Gilang Pratama; Sukaesih Sukaesih; Samson CMS (Jurnal Informatio, 2021)
The world is now facing the phenomenon of hypercompetition, where working procedure is required to change to be more dynamic and modern. This phenomenon covers all aspects, including Indonesian library world and Indonesian literacy. Faced with new problems, Indonesian library world and Indonesian literacy has actually been trying to solve its old issue: the low level of Indonesian literacy. Community Reading Park (TBM) exists with the aim of increasing the level of Indonesian literacy. However, many newly established TBMs tend to be static and traditional, which are no longer relevant to modern times. West Java Community Reading Park Forum (West Java FTBM) is present to help TBMs stay relevant with present situation. In its activities, West Java FTBM applies Knowledge Management in general and Knowledge Sharing in particular. This study examines the role of Knowledge Sharing and how much it relates to innovation in TBM managers. Knowledge Sharing itself has two dimensions, namely; Knowledge Donating and Knowledge Collecting. The population in this study was West Java FTBM, with a sample of 67 TBM managers. The method used was quantitative with correlational analysis, and hypotheses testing was done by testing Knowledge Donating, Collecting, and Sharing with Manager’s Innovations. The research results of Knowledge Donating, Collecting, and Sharing each had relationship with Manager’s Innovation, with the coefficient of determination, sequentially, 17.47%; 20.88%; and 27.66%. This shows that Manager’s Innovation in West Java FTBM was not created solely because of Knowledge Sharing, but many other factors affected it, one of which is the length of one's experience in managing TBM. In the future, the implementation of Knowledge Sharing in West Java FTBM is expected to be even more dynamic by expanding references to things innovated and collaborating with other communities, this is to add a new point of view for TBM Managers in West Java FTBM